Mechanism of Hedyotis Diffusa in the Treatment of Cervical Cancer - Qian, Kai; Fu, Dan; Jiang, Baorui; Wang, Yue; Tian, Fei; Song, Li; Li, Lei (Frontiers in Pharmacology, 2021)
Cervical cancer is one of the most common malignant tumors among women in the world. In clinical practice, Hedyotis diffusa has pharmacological effects in treating cervical cancer, but its components are relatively complex, and the mechanism of Hedyotis diffusa in treating cervical cancer is still unclear. In this work, the potential active components and mechanism of Hedyotis diffusa in the treatment of cervical cancer were explored by means of network pharmacology. By constructing its active ingredient-target network, and enriching and analyzing the targets, we found the key targets and their effective components (beta-Sitosterol and Quercetin) that play a therapeutic role. Finally, we evaluated the prognostic value of the core target genes through survival analysis. Our work explains the mechanism of Hedyotis diffusa in treatment of cervical cancer, which lays a theoretical foundation for further exploring its pharmacological action and its clinical application.